The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1523/jneurosci.1711-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Synaptic Rac1 Activity, Long-Term Potentiation Maintenance, and Learning and Memory by BCR and ABR Rac GTPase-Activating Proteins

Abstract: Rho family small GTPases are important regulators of neuronal development. Defective Rho regulation causes nervous system dysfunctions including mental retardation and Alzheimer’s disease. Rac1, a member of the Rho family, regulates dendritic spines and excitatory synapses, but relatively little is known about how synaptic Rac1 is negatively regulated. Breakpoint cluster region (BCR) is a Rac GTPase-activating protein known to form a fusion protein with the c-Abl tyrosine kinase in Philadelphia chromosome-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 87 publications
7
109
0
1
Order By: Relevance
“…We found that BCR expression decreases through development (Fig. 5, B and C), which is supported by Oh et al (9), who observed decreased levels of BCR expression as mice age. It is tempting to speculate that this differential expression may be due to mutual regulation, although this remains to be investigated.…”
Section: The Ptb Domain Of Sh2d5 Interacts With a Specific Nxxf Motifsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that BCR expression decreases through development (Fig. 5, B and C), which is supported by Oh et al (9), who observed decreased levels of BCR expression as mice age. It is tempting to speculate that this differential expression may be due to mutual regulation, although this remains to be investigated.…”
Section: The Ptb Domain Of Sh2d5 Interacts With a Specific Nxxf Motifsupporting
confidence: 89%
“…Because of the shared domain architecture of SH2D5 with Tyr(P) recognition adaptor proteins, we reasoned that a first step in unraveling the function of SH2D5 would be to analyze its interaction profiles in unstimulated cells and cells in which tyrosine phosphorylation is induced by exposure to pervanadate. Here, we characterize a novel interaction of the SH2D5 PTB domain with breakpoint cluster region protein (BCR), a regulator of Rho GTPases (9,10). We show enrichment of SH2D5 and BCR proteins in neuronal cell types.…”
Section: a And B)mentioning
confidence: 97%
“…Some papers have reported that manipulations of the hippocampus impair novel object preference tasks (Mansuy et al, 1998;Pittenger et al, 2002;Oh et al, 2010). However, in a number of these studies such variation may be accounted for by differences in the experimental paradigms used, in particular the type or number of stimuli presented in the sample phase.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA, Rac and Cdc42 are the three best-studied Rho GTPases, which control the formation of distinct F-actin-based structures [39,40] . Studies have shown that RhoA and Rac1 are important for structural aspects of the mature neuron [41] and are related to learning and memory [42,43] . The present study set about to explore the relationship between the small Rho GTPases and drug withdrawal-induced hippocampal actin polymerization.…”
Section: Discussionmentioning
confidence: 99%